Analisis Nilai Religi Dalam Cerita Rakyat Tradisi Meron - Nurul Aini; Ayunda Choirun Nisa; Adira Thifalanajla Khairunnisa; Elyana Rosyita; Mohammad khanzunnudin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to analyze the narrative structure and religious values ​​contained in the oral stories of the Meron Tradition. This research was designed qualitatively and used an analytical method based on Axel Olrix's theory. The results of the analysis show that the Meron Tradition oral stories prioritize narrative structure to build the storyline. The author uses literature study techniques to collect data by reading, taking notes, and processing research materials. They also use Triagulation techniques to ensure the validity of the data. Triangulation uses something other than the data for checking or comparison. The narrative structure in the Meron Tradition oral story is an interrelated and interdependent component. One of the religious values ​​in the Meron Tradition story is worship, gratitude, trust, respect and the example of the Prophet Muhammad SAW.